SUPPLY CHAIN RICE SEEDS AT MALANG REGENCY: SUPPLY CHAIN MACRO PROCESSES - AULIA RAHARJA (Agricultural Socio-Economics Journal, 2018)
The aim of this research is to analyze relationship performance between producer and farmer partner of first level of paddy seed commodity in Malang Regency, analyze relationship performance between farmer of first level partner and farmer of mktra second level of paddy seed commodity in Malang Regency, analyze relationship performance between producer and shop agricultural commodities of paddy seeds in Malang Regency, analyze the performance of relation between agricultural store and consumer of rice seed commodity store in Malang Regency. Determination of sampling method is by multistage sampling and snowball sampling in accordance with information from BPSB (Seed Overseeing and Certification Agency) which has criteria of largest rice seed producer and its marketing area is biggest. Meanwhile, descriptive statistics with in-depth interviews were used in this study to analyze the importance of indicators in considering linkages with rice seed suppliers. These indicators have several sub-indicators that have been divided into five scales: totally unimportant, unimportant, important, important, and very important. There is a close relation performance between producer and farmer of first level partner whereas mutual relation which happened between farmer of first level partner to producer also has a close relation performance. For the performance of the relationship between the first level farmers and the second level farmers, there is a fairly close relationship, whereas the performance of mutual relations between the second level farmers to the first level partner farmers has a close relationship. Related to the performance of relationships between producers to agricultural stores have a close relationship, while the performance of farm shop relations to producers is said to be very close.